Silicon carbide composite seed crystal and method of making same, silicon carbide crystal
Patent Information
- Application Number
- CN202510535579.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-04-27
AI Technical Summary
[0006]本申请的目的在于提供碳化硅复合籽晶的制备方法,用于解决碳化硅材料的低热导率不利于形成碳化硅晶体所需要的在垂直方向大的温度梯度,因此碳化硅晶体的生长速度不仅慢,生长厚度也非常小,即碳化硅晶体长不厚,厚度一般仅为20~25mm,或者在长厚的情况下晶体内部质量差,无法得到电子级的碳化硅晶体的问题;通过本申请方法制备的碳化硅复合籽晶在实现大直径、高厚度、低成本的碳化硅晶体的生长的同时,还能保证碳化硅晶体的生长质量
[0014]通过在高热导率的金刚石基片的表面上形成低热导率的碳化硅过渡层,使金刚石基片的表面与碳化硅过渡层的碳面通过碳原子扩散结合,降低了界面应力,增强了两相的结合强度;通过在低热导率的碳化硅过渡层的硅面上形成更低热导率的碳化硅籽晶,使碳化硅过渡层作为热应力缓冲层,减少因金刚石基片与碳化硅籽晶之间的热膨胀系数差异而导致的界面裂纹或剥离。
Smart Images

Figure CN120401009B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of semiconductor material preparation, and in particular to silicon carbide composite seed crystals and their preparation methods, as well as silicon carbide crystals including the silicon carbide composite seed crystals. Background Technology
[0002] Silicon carbide crystals, due to their wide bandgap, high thermal conductivity, and high breakdown field strength, are widely used in electric vehicles, photovoltaics, and radio frequency communications, making them one of the most important third-generation semiconductor materials. Because of their high optical refractive index and high thermal conductivity, silicon carbide crystals are currently being used as optical chips in augmented reality (AR) glasses, with a very broad market application prospect.
[0003] Silicon carbide single crystals are typically produced as large-size, commercially viable bulk crystals using PVT (Physical Vapor Transport) and LPE (Liquid Phase Epitaxy). However, the growth rate is significantly lower than that of silicon crystals. Currently, silicon carbide single crystals are mainly available in 6-inch and 8-inch diameters, with a single crystal growth cycle of approximately 7-10 days. The growth rate is extremely slow; most domestic manufacturers achieve growth rates of 100-150 micrometers per hour, resulting in single crystal thicknesses of only 20-25 mm. The yield rate is far lower than that of mature single-crystal silicon growth, and the growth process is often described as a "black box" operation, with opaque ingots and no timely quality feedback. Wolfspeed, an American company, has achieved a world-leading growth rate of over 300 micrometers per hour on its silicon carbide substrates, reaching a thickness of 60 mm, in mass production of 8-inch ingots.
[0004] The slow growth rate of silicon carbide crystals is due to the poor physical properties of the silicon carbide single-crystal seed crystals used in both physical vapor deposition (PVD) and flux-driven liquid phase (CFLD) methods. Traditional seed crystals consist of a certain thickness of silicon carbide single-crystal material, whose thermal conductivity is only 490 W / (m·K). Factors affecting the thermal conductivity of silicon carbide single crystals include impurities and crystal structure defects. For example, an increase in nitrogen content reduces the material's thermal conductivity, and the presence of crystal structure defects leads to a decrease in thermal conductivity. During crystal growth, the temperature gradient is the intrinsic driving force for single-crystal crystallization and a key factor determining the crystal growth rate. There is a close positive correlation between crystal growth rate and temperature gradient; a larger temperature gradient results in a faster crystallization rate, and vice versa. The low thermal conductivity of silicon carbide materials is not conducive to the formation of a large temperature gradient in the vertical direction required for silicon carbide crystals. Therefore, the growth rate of silicon carbide crystals is not only slow, but the growth thickness is also very small. That is, silicon carbide crystals are not thick, and the thickness is generally only 20 to 25 mm. Or, if they are thick, the internal quality of the crystal is poor, and electronic-grade silicon carbide crystals cannot be obtained.
[0005] This application addresses at least one of the above-mentioned problems. Summary of the Invention
[0006] The purpose of this application is to provide a method for preparing silicon carbide composite seed crystals, which solves the problem that the low thermal conductivity of silicon carbide material is not conducive to the formation of silicon carbide crystals, which requires a large temperature gradient in the vertical direction. As a result, the growth rate of silicon carbide crystals is not only slow, but the growth thickness is also very small. That is, the silicon carbide crystals are not thick, and the thickness is generally only 20-25 mm. Or, if they are thick, the internal quality of the crystal is poor, and it is impossible to obtain electronic-grade silicon carbide crystals. The silicon carbide composite seed crystals prepared by the method of this application can achieve the growth of large-diameter, high-thickness, and low-cost silicon carbide crystals, while also ensuring the growth quality of silicon carbide crystals.
[0007] To achieve the above objectives, this application adopts the following technical solution:
[0008] The first aspect of this application provides a method for preparing silicon carbide composite seed crystals, comprising the following steps:
[0009] Provide diamond substrates;
[0010] A silicon carbide transition layer is formed on the surface of the diamond substrate, and the silicon surface of the silicon carbide transition layer is moved away from the surface of the diamond substrate to obtain a diamond / silicon carbide composite structure.
[0011] A silicon carbide seed crystal is formed on the silicon surface of the diamond / silicon carbide composite structure, and the carbon surface of the silicon carbide seed crystal is moved away from the silicon surface of the silicon carbide transition layer to obtain a silicon carbide composite seed crystal.
[0012] The thermal conductivity of the silicon carbide transition layer is less than that of the diamond substrate, and the thermal conductivity of the silicon carbide transition layer is greater than that of the silicon carbide seed crystal; the crystal form of the silicon carbide transition layer is different from that of the silicon carbide seed crystal.
[0013] Compared with the prior art, the beneficial effects of this application are as follows:
[0014] By forming a low thermal conductivity silicon carbide transition layer on the surface of a high thermal conductivity diamond substrate, the surface of the diamond substrate and the carbon surface of the silicon carbide transition layer are bonded through carbon atom diffusion, which reduces interfacial stress and enhances the bonding strength between the two phases. By forming an even lower thermal conductivity silicon carbide seed crystal on the silicon surface of the low thermal conductivity silicon carbide transition layer, the silicon carbide transition layer acts as a thermal stress buffer layer, reducing interfacial cracks or peeling caused by the difference in thermal expansion coefficients between the diamond substrate and the silicon carbide seed crystal.
[0015] By establishing a temperature gradient between a high thermal conductivity diamond substrate, a low thermal conductivity silicon carbide transition layer, and an even lower thermal conductivity silicon carbide seed crystal, heat can be rapidly transferred from the silicon carbide seed crystal along both the vertical and horizontal directions. This results in a large temperature gradient in both the vertical and horizontal directions of the silicon carbide composite seed crystal. This not only increases the growth rate of the silicon carbide crystal in the vertical direction, which is beneficial for growing silicon carbide crystals with a thickness of more than 50 mm, but also increases the growth rate of the silicon carbide crystal in the horizontal direction, which is beneficial for increasing the diameter of the silicon carbide crystal during growth and facilitating the growth of large-diameter silicon carbide crystals. This significantly reduces the growth cost of silicon carbide materials. In summary, the silicon carbide composite seed crystal prepared by the above method can achieve the growth of large-diameter, high-thickness, and low-cost silicon carbide crystals while ensuring the growth quality of the silicon carbide crystals.
[0016] In some possible embodiments of the first aspect, during the formation of the silicon carbide transition layer on the surface of the diamond substrate, the surface of the diamond substrate and the carbon facet of the silicon carbide transition layer are bonded by carbon atom diffusion; the formation of the silicon carbide transition layer on the surface of the diamond substrate includes:
[0017] The silicon carbide transition layer is prepared by chemical vapor deposition on the surface of the diamond substrate under the conditions of temperature 850-900℃, gas pressure 20-30Kpa, flow rate of SiH4 and CH4 2-20sccm, and flow rate of H2 200-500sccm; wherein the growth time of the silicon carbide transition layer is 10-20h.
[0018] In some possible embodiments of the first aspect, during the formation of the silicon carbide transition layer on the surface of the diamond substrate, the surface of the diamond substrate and the carbon facet of the silicon carbide transition layer are bonded by carbon atom diffusion; the formation of the silicon carbide transition layer on the surface of the diamond substrate includes:
[0019] Under conditions of temperature of 1900–2100℃ and pressure of 0.001–0.03 Pa, the surface of the diamond substrate is heterobonded to the carbon surface of the initial silicon carbide transition layer to obtain a first heterobonded structure.
[0020] After heterobonding is completed, the first heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen to form the silicon carbide transition layer.
[0021] In some possible embodiments of the first aspect, during the formation of a silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure, the silicon surface of the silicon carbide transition layer and the silicon surface of the silicon carbide seed crystal are bonded together by silicon atom diffusion; the formation of the silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure includes:
[0022] The silicon carbide seed crystal is prepared by chemical vapor deposition on the surface of the diamond / silicon carbide composite structure under the conditions of temperature 850-900℃, gas pressure 20-30Kpa, flow rate of SiH4 and CH4 2-20sccm, and flow rate of H2 200-500sccm; wherein the growth time of the silicon carbide seed crystal is 10-20h.
[0023] In some possible embodiments of the first aspect, during the formation of a silicon carbide seed crystal on the silicon surface of the silicon carbide composite structure, the silicon surface of the silicon carbide transition layer and the silicon surface of the silicon carbide seed crystal are bonded together by silicon atom diffusion; the formation of the silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure includes:
[0024] Under conditions of temperature of 1900–2100℃ and pressure of 0.001–0.03 Pa, the silicon facet of the diamond / silicon carbide composite structure is heterobonded to the silicon facet of the initial silicon carbide seed crystal to obtain a second heterobonded structure.
[0025] After heterobonding is completed, the second heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen to form the silicon carbide seed crystal.
[0026] In some possible embodiments of the first aspect, after forming the silicon carbide transition layer, the method further includes:
[0027] A groove-shaped first microchannel is formed on the silicon surface of the silicon carbide transition layer; or a raised first microchannel is formed on the silicon surface of the silicon carbide transition layer.
[0028] Wherein, the width of the first microchannel is 5-10 μm; and / or the depth of the first microchannel is 30-50 μm; and / or the lateral spacing of the first microchannel is 5-10 mm.
[0029] In some possible embodiments of the first aspect, prior to forming the silicon carbide seed crystal, the method further includes:
[0030] A groove-shaped second microchannel is formed on the silicon surface of the initial silicon carbide seed crystal; or a raised second microchannel is formed on the silicon surface of the initial silicon carbide seed crystal.
[0031] Wherein, the width of the second microchannel is 5-10 μm; and / or the depth of the second microchannel is 30-50 μm; and / or the lateral spacing of the second microchannel is 5-10 mm;
[0032] The raised second microchannel corresponds to the grooved first microchannel, so that the raised second microchannel can be embedded in the grooved first microchannel;
[0033] The raised first microchannel corresponds to the grooved second microchannel, so that the raised first microchannel can be embedded in the grooved second microchannel.
[0034] In some possible embodiments of the first aspect, the diamond substrate is a single-crystal diamond or a polycrystalline diamond;
[0035] And / or, the thickness of the diamond substrate is 300–500 μm;
[0036] And / or, the thickness of the diamond substrate is less than or equal to two-thirds of the thickness of the silicon carbide composite seed crystal, and the thickness of the diamond substrate is greater than or equal to one-half the thickness of the silicon carbide composite seed crystal.
[0037] And / or, the surface roughness of the diamond substrate is less than a first preset roughness, the first preset roughness being in the range of 1 to 5 nm.
[0038] And / or, the silicon carbide material in the silicon carbide transition layer is of 3C, 4H, 6H or 15R crystal form;
[0039] And / or, the thickness of the silicon carbide transition layer is 10–50 μm;
[0040] And / or, the surface roughness of the silicon surface of the silicon carbide transition layer is less than the second preset roughness, and the value of the second preset roughness is in the range of 1 to 5 nm;
[0041] And / or, the thickness of the silicon carbide seed crystal is 100-200 μm;
[0042] And / or, the thickness of the silicon carbide seed crystal is less than one-third of the thickness of the silicon carbide composite seed crystal;
[0043] And / or, the surface roughness of the silicon surface of the silicon carbide seed crystal is less than a third preset roughness, the value of which is in the range of 1 to 5 nm.
[0044] In a second aspect, this application provides a silicon carbide composite seed crystal, which is prepared by the aforementioned method for preparing silicon carbide composite seed crystals.
[0045] A third aspect of this application provides a silicon carbide crystal comprising the aforementioned silicon carbide composite seed crystal. Attached Figure Description
[0046] Figure 1 A flowchart illustrating the overall steps of the method for preparing silicon carbide composite seed crystals provided in this application;
[0047] Figure 2 This is a schematic diagram of the structure of the silicon carbide composite seed crystal provided in this application;
[0048] Figure 3 A schematic diagram of the first and second microchannels provided in this application, which are arranged in a vortex-shaped mosquito coil pattern.
[0049] In the figure, 10 is a silicon carbide composite seed crystal; 11 is a diamond substrate; 12 is a silicon carbide transition layer; and 13 is a silicon carbide seed crystal. Detailed Implementation
[0050] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided to make this application more complete and comprehensive, and to fully convey the concept of the exemplary embodiments to those skilled in the art. The same reference numerals in the drawings denote the same or similar structures, and therefore repeated descriptions of them will be omitted.
[0051] The terms used in this application to express position and direction are illustrated with the accompanying drawings, but may be changed as needed, and all such changes are included within the scope of protection of this application.
[0052] In a first aspect, this embodiment provides a method for preparing silicon carbide composite seed crystals, combined with... Figure 1 As shown, it includes the following steps S1-S3.
[0053] Step S1: Provide a diamond substrate.
[0054] The surface roughness of the diamond substrate is less than a first preset roughness, which ranges from 1 to 5 nm. For example, the surface roughness of the diamond substrate can be 0.5 nm, 1 nm, 2 nm, 3 nm or 4 nm.
[0055] It should be noted that the thickness of the diamond substrate is 300–500 μm, for example, it can be 300 μm, 350 μm, 400 μm, 450 μm or 500 μm; the thickness of the diamond substrate is less than or equal to two-thirds of the thickness of the silicon carbide composite seed crystal, and the thickness of the diamond substrate is greater than or equal to one-half the thickness of the silicon carbide composite seed crystal.
[0056] By controlling the thickness of the diamond substrate within the above range, the overall thermal conductivity of the prepared silicon carbide composite seed crystal is more than 40% higher than that of the pure silicon carbide seed crystal. The temperature gradient of the silicon carbide composite seed crystal can be increased by 15-20% in the vertical direction and by 10% in the horizontal direction.
[0057] This application does not specifically limit the diamond substrate; any suitable diamond substrate in the art can be used to implement the technical solutions of this application. In some embodiments of this application, the diamond substrate used can be selected from single-crystal diamond or polycrystalline diamond, preferably single-crystal diamond.
[0058] Furthermore, as a preferred embodiment of this application, the preparation method further includes steps S11-S14 before forming the silicon carbide transition layer.
[0059] Step S11: Polish the surface of the diamond substrate.
[0060] For example, the surface of a diamond substrate can be polished by mechanical grinding to reduce its surface roughness to less than 1–5 nm. For instance, the surface roughness of the diamond substrate can be 0.5 nm, 1 nm, 2 nm, 3 nm, or 4 nm.
[0061] Step S12: Acid washing is performed on the polished diamond substrate.
[0062] For example, a diamond substrate can be pickled by soaking it in aqua regia (a mixture of nitric acid and hydrochloric acid) for 30 minutes to remove contaminant particles from the surface of the diamond substrate.
[0063] Step S13: Perform ultrasonic cleaning on the acid-washed diamond substrate.
[0064] For example, ultrasonic cleaning of a diamond substrate with acetone solution for 10 minutes can penetrate deep into the microporous structure of the diamond substrate surface, achieving thorough cleaning without dead angles. This not only further removes contaminant particles from the diamond substrate surface but also creates micro-scratches on the surface, optimizing its morphology and thus improving the nucleation density and adhesion to the subsequent silicon carbide transition layer, allowing the nucleation density to reach up to 10. 9 / cm 2 .
[0065] Step S14: Dry the ultrasonically cleaned diamond substrate. For example, bake the diamond substrate in an oven at 200°C for 15 minutes to dry it.
[0066] Through the above steps, efficient decontamination of the diamond substrate is achieved, ensuring the integrity and high cleanliness of its surface. This reduces defects caused by contaminants during the subsequent formation of the silicon carbide transition layer, ensuring that the number of particles (0.3μm scale) on the diamond substrate surface is less than 500-1000, thus ensuring the uniformity and adhesion of the silicon carbide transition layer on the diamond substrate surface.
[0067] Step S2: A silicon carbide transition layer is formed on the surface of the diamond substrate, and the silicon surface of the silicon carbide transition layer is moved away from the surface of the diamond substrate to obtain a diamond / silicon carbide composite structure.
[0068] The thickness of the silicon carbide transition layer is 10 to 50 μm, for example, it can be 10 μm, 20 μm, 30 μm, 40 μm or 50 μm; the surface roughness of the silicon surface of the silicon carbide transition layer is less than a second preset roughness, the value of the second preset roughness is in the range of 1 to 5 nm, for example, the surface roughness of the silicon surface of the silicon carbide transition layer can be 0.5 nm, 1 nm, 2 nm, 3 nm or 4 nm.
[0069] It should be noted that the thermal conductivity of the silicon carbide transition layer is lower than that of the diamond substrate. For the silicon carbide transition layer, the silicon carbide material in the transition layer can be 3C, 4H, 6H, or 15R crystal forms, etc., and in this embodiment, the 3C crystal form is preferred.
[0070] It should be further explained that during the formation of the silicon carbide transition layer on the surface of the diamond substrate, the surface of the diamond substrate and the carbon surface of the silicon carbide transition layer are bonded together through carbon atom diffusion. Since the carbon atoms of the diamond substrate and the carbon atoms of the silicon carbide transition layer are bonded together by forming covalent bonds, there is no intermediate transition layer between them, making the bond between them even tighter.
[0071] Furthermore, as a preferred embodiment of this application, forming a silicon carbide transition layer on the surface of a diamond substrate includes steps S21a-S22a.
[0072] Step S21a: Under the conditions of temperature of 1900~2100℃ and air pressure of 0.001~0.03pa, the surface of the diamond substrate is heterobonded with the carbon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0073] The temperature can be 1900℃, 1950℃, 2000℃, 2050℃ or 2100℃; the air pressure can be 0.001pa, 0.005pa, 0.01pa, 0.015pa, 0.02pa, 0.025pa or 0.03pa.
[0074] Through in-depth research, the inventors discovered that during heterogeneous bonding, if the temperature is below 1900℃, the bonding is weak and defects such as voids and microcracks are easily generated at the interface; if the temperature is above 2100℃, power consumption is excessive and it has little effect on improving the bonding strength. If the gas pressure is above 0.03Pa, the vacuum level is not high, and impurities such as air are easily introduced, affecting the bonding effect; if the gas pressure is below 0.001Pa, the requirements for system equipment are very high, resulting in high costs. Therefore, it is necessary to control the temperature and gas pressure of heterogeneous bonding within the above-mentioned ranges.
[0075] Under the aforementioned conditions, heterogeneous bonding (with all bonding surfaces being carbon surfaces) results in a small lattice mismatch between the silicon carbide transition layer and the diamond substrate, leading to a very low solid-solid interface energy. This facilitates interlayer-free silicon carbide bonding, promoting chemical bond formation, reducing interface defect density, and ensuring close surface contact, thus minimizing micropores and gaps and improving the compactness and mechanical strength of the first heterogeneous bonding structure. Furthermore, it reduces residual interfacial stress caused by the thermal expansion difference between the silicon carbide transition layer and the diamond substrate, preventing cracking of the second heterogeneous bonding structure. Additionally, under these conditions, the low interfacial thermal resistance and high thermal conductivity of diamond allow for rapid heat conduction away from the silicon carbide transition layer, thereby establishing a larger temperature gradient in both the vertical and horizontal directions within the silicon carbide composite seed crystal.
[0076] Step S22a: After heterobonding is completed, the first heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen to form a silicon carbide transition layer.
[0077] The annealing temperature can be 1800℃, 1820℃, 1850℃, 1880℃ or 1900℃; the annealing time can be 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h or 40h.
[0078] The inventors discovered that annealing below 1800℃, exceeding the aforementioned temperature range, results in poor removal of thermal stress and fails to effectively eliminate the thermal stress generated by bonding. Annealing at 1900℃ effectively removes internal thermal stress; further increases in temperature lead to high electricity costs and are not worthwhile. Similarly, the annealing time also needs to be controlled within the aforementioned range. Therefore, it is necessary to control the annealing temperature and time within the aforementioned range.
[0079] By annealing the first heterogeneous bonding structure under the above conditions, not only can the internal thermal stress generated during the bonding process be reduced, but the physical diffusion of carbon atoms can also be promoted at high temperature, thereby reducing the interfacial thermal resistance.
[0080] As another preferred embodiment of this application, forming a silicon carbide transition layer on the surface of a diamond substrate includes step S21b.
[0081] Step S21b: Under the conditions of a temperature of 850-900℃, a gas pressure of 20-30Kpa, a flow rate of 2-20sccm for both SiH4 and CH4, and a flow rate of 200-500sccm for H2, a silicon carbide transition layer is prepared by chemical vapor deposition on the surface of a diamond substrate.
[0082] The growth time of the silicon carbide transition layer is 10–20 h, for example, 10 h, 12 h, 15 h, 18 h, or 20 h. The temperature can be 850℃, 860℃, 870℃, 880℃, 890℃, or 900℃; the gas pressure can be 20 kPa, 22 kPa, 25 kPa, 28 kPa, or 30 kPa; the flow rates of SiH4 and CH4 can be 2 sccm, 4 sccm, 6 sccm, 8 sccm, 10 sccm, 12 sccm, 14 sccm, 16 sccm, 18 sccm, or 20 sccm; the flow rate of H2 can be 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, or 500 sccm; the purity of SiH4, CH4, and H2 can be 99.9999%.
[0083] The inventors discovered that during the chemical vapor deposition (CVD) growth of silicon carbide transition layers, growth is very slow if the temperature is below 850°C; while growth is faster if the temperature is above 900°C, the quality of the resulting silicon carbide transition layer is poor. If the pressure is below 20 kPa, the plasma power density is low, resulting in a slow growth rate; while if the pressure is above 30 kPa, the plasma density is high, leading to a faster growth rate, but also increasing the likelihood of amorphous carbides forming.
[0084] SiH4 and CH4 are the feed gases for chemical vapor deposition (CVD) growth of silicon carbide. If the concentration is too low (flow rate less than 2 sccm), the growth rate is very slow; if the concentration is too high (flow rate greater than 20 sccm), although the growth rate is fast, the quality of the grown silicon carbide material is very poor. Hydrogen is used as a carrier gas for the feed gases and can etch amorphous silicon carbide in a timely manner. If the concentration is too low (flow rate less than 200 sccm), the growth rate is very slow; if the concentration is too high (flow rate greater than 500 sccm), hydrogen will etch away other amorphous carbide materials.
[0085] If the growth time of the silicon carbide transition layer is too short (less than 10 hours), a silicon carbide transition layer of a certain thickness cannot be produced; if the growth time is too long (more than 20 hours), the quality of the silicon carbide transition layer will be low, which is not conducive to the preparation of silicon carbide composite seed crystals.
[0086] Using the above conditions to prepare a silicon carbide transition layer on the surface of a diamond substrate by chemical vapor deposition not only provides a good material basis for the silicon carbide transition layer and silicon carbide seed crystal to grow or bond homogeneously, but also prevents dislocation defects inside the diamond from extending to the silicon carbide seed crystal, thereby avoiding affecting the quality of the grown silicon carbide crystal.
[0087] Furthermore, as a preferred embodiment of this application, after forming the silicon carbide transition layer, the preparation method further includes step S23.
[0088] Step S23: Etch a groove-shaped first microchannel or a raised first microchannel on the silicon surface of the silicon carbide transition layer.
[0089] For preferred options, please refer to the appendix. Figure 3 As shown, the first microchannel is vortex-shaped (mosquito coil pattern), and the etching width of the first microchannel is 5-10 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm; the etching depth of the first microchannel is 30-50 μm, for example, it can be 30 μm, 35 μm, 40 μm, 45 μm or 50 μm; the lateral spacing of the first microchannel is 5-10 mm, for example, it can be 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0090] Furthermore, as a preferred embodiment of this application, the preparation method further includes steps S24-S27 before forming the silicon carbide seed crystal.
[0091] Step S24: Polish the silicon surface of the silicon carbide transition layer in the diamond / silicon carbide composite structure.
[0092] For example, the silicon surface of the silicon carbide transition layer is polished by mechanical grinding to make its surface roughness less than 1-5 nm.
[0093] Step S25: Acid-wash the polished diamond / silicon carbide composite structure.
[0094] For example, the diamond / silicon carbide composite structure was pickled by soaking it in aqua regia (a mixture of nitric acid and hydrochloric acid) for 30 minutes to remove contaminant particles from the silicon surface of the silicon carbide transition layer.
[0095] Step S26: Perform ultrasonic cleaning on the acid-washed diamond / silicon carbide composite structure.
[0096] For example, ultrasonic cleaning of diamond / silicon carbide composite structures with acetone solution for 10 minutes can penetrate deep into the micropores of the diamond / silicon carbide composite structure, achieving thorough cleaning without dead angles. This not only further removes contaminating particles from the surface of the diamond / silicon carbide composite structure but also creates micro-scratches on the surface, optimizing its surface morphology. This, in turn, increases the nucleation density and bonding strength with subsequent silicon carbide seed crystals, allowing the nucleation density to reach up to 10. 9 / cm 2 .
[0097] Step S27: Dry the ultrasonically cleaned diamond / silicon carbide composite structure.
[0098] For example, the diamond / silicon carbide composite structure can be dried by baking it in an oven at 200°C for 15 minutes.
[0099] Through the above steps, efficient decontamination of the diamond / silicon carbide composite structure is achieved, ensuring the integrity and high cleanliness of its surface. This reduces defects caused by contaminants during the subsequent formation of silicon carbide seed crystals, ensuring that the number of particles (0.3μm scale) on the surface of the diamond / silicon carbide composite structure is less than 500-1000, thus ensuring the uniformity and adhesion of the silicon carbide seed crystals on the silicon surface of the silicon carbide transition layer.
[0100] Furthermore, as a preferred embodiment of this application, the preparation method further includes steps S24b-S27b before forming the silicon carbide seed crystal.
[0101] Step S24b: Polish the silicon surface of the silicon carbide seed crystal.
[0102] For example, the silicon surface of the silicon carbide seed crystal is polished by mechanical grinding to make its surface roughness less than a third preset roughness, the value of which ranges from 1 to 5 nm. The surface roughness of the silicon surface of the silicon carbide seed crystal can be, for example, 0.5 nm, 1 nm, 2 nm, 3 nm, or 4 nm.
[0103] Step S25b: Acid washing is performed on the polished silicon carbide seed crystal.
[0104] For example, soaking silicon carbide seed crystals in aqua regia (a mixture of nitric acid and hydrochloric acid) for 30 minutes can remove contaminant particles from the silicon surface of the silicon carbide seed crystals.
[0105] Step S26b: Perform ultrasonic cleaning on the acid-washed silicon carbide seed crystal.
[0106] For example, ultrasonic cleaning of silicon carbide seed crystals with acetone solution for 10 minutes can penetrate deep into the microporous structure of the silicon carbide seed crystal surface, achieving thorough cleaning without dead angles. This not only further removes contaminant particles from the silicon carbide seed crystal surface but also creates micro-scratches on the surface, optimizing its surface morphology. This, in turn, improves the nucleation density and bonding strength with the subsequent diamond / silicon carbide composite structure, allowing the nucleation density to reach up to 10. 9 / cm 2 .
[0107] Step S27b: Dry the ultrasonically cleaned silicon carbide seed crystal.
[0108] For example, the silicon carbide seed crystal is dried by baking it in an oven at 200°C for 15 minutes.
[0109] Through the above steps, efficient decontamination of silicon carbide seed crystals is achieved, ensuring the integrity and high cleanliness of their surface. This reduces defects caused by contaminants during the subsequent formation of silicon carbide seed crystals, ensuring that the number of particles (0.3μm scale) on the surface of the silicon carbide seed crystal is less than 500-1000, thus ensuring the uniformity and adhesion of the silicon carbide seed crystal on the silicon surface of the silicon carbide transition layer.
[0110] Furthermore, as a preferred embodiment of this application, the preparation method further includes step S28 before forming the silicon carbide seed crystal (which may be heterobonding between the silicon surface of the diamond / silicon carbide composite structure and the silicon surface of the initial silicon carbide seed crystal).
[0111] Step S28: Etch a groove-shaped second microchannel or a raised second microchannel on the silicon surface of the initial silicon carbide seed crystal.
[0112] For preferred options, please refer to the appendix. Figure 3 As shown, the second microchannel is vortex-shaped (mosquito coil pattern), and the etching width of the second microchannel is 5-10 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm; the etching depth of the second microchannel is 30-50 μm, for example, it can be 30 μm, 35 μm, 40 μm, 45 μm or 50 μm; the lateral spacing of the second microchannel is 5-10 mm, for example, it can be 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0113] It should be noted that the raised second microchannel corresponds to the grooved first microchannel so that the raised second microchannel can be embedded in the grooved first microchannel; the raised first microchannel corresponds to the grooved second microchannel so that the raised first microchannel can be embedded in the grooved second microchannel.
[0114] The corresponding interlocking of the first and second microchannels can increase the contact surface area between the silicon carbide seed crystal and the silicon carbide transition layer during the bonding process, thereby enhancing the heat transfer capability of the silicon carbide seed crystal and the silicon carbide transition layer during the growth process, which helps to establish a larger temperature gradient in the vertical and horizontal directions for the silicon carbide composite seed crystal.
[0115] Step S3: Form a silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure, and move the carbon surface of the silicon carbide seed crystal away from the silicon surface of the silicon carbide transition layer to obtain a silicon carbide composite seed crystal.
[0116] The thickness of the silicon carbide seed crystal is 100-200 μm, for example, it can be 100 μm, 120 μm, 150 μm, 180 μm or 200 μm.
[0117] It should be noted that the thickness of the silicon carbide seed crystal is less than one-third the thickness of the silicon carbide composite seed crystal.
[0118] By controlling the thickness of the silicon carbide seed crystal within the above range, the overall thermal conductivity of the prepared silicon carbide composite seed crystal can be more than 40% higher than that of the pure silicon carbide seed crystal. The temperature gradient of the silicon carbide composite seed crystal increases by 15-20% in the vertical direction and by 10% in the horizontal direction.
[0119] It should be noted that the thermal conductivity of the silicon carbide transition layer is greater than that of the silicon carbide seed crystal; the crystal form of the silicon carbide transition layer is different from that of the silicon carbide seed crystal. The silicon carbide material in the silicon carbide seed crystal can be 3C, 4H, 6H or 15R crystal forms, etc., and the 4H crystal form is preferred in this embodiment.
[0120] It should be further explained that during the formation of the silicon carbide seed crystal on the silicon facet of the diamond / silicon carbide composite structure, the silicon facet of the silicon carbide transition layer and the silicon facet of the silicon carbide seed crystal are bonded together through silicon atom diffusion. Since the silicon atoms in the silicon carbide transition layer and the silicon atoms in the silicon carbide seed crystal are bonded together through covalent bonds, there is no intermediate transition layer between them, making their bonding even tighter.
[0121] Furthermore, as a preferred embodiment of this application, forming a silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure includes steps S31a-S32a.
[0122] Step S31a: Under the conditions of temperature of 1900~2100℃ and pressure of 0.001~0.03pa, the silicon face of the diamond / silicon carbide composite structure is heterobonded with the silicon face of the initial silicon carbide seed crystal to obtain the second heterobonded structure.
[0123] The temperature can be 1900℃, 1950℃, 2000℃, 2050℃ or 2100℃; the air pressure can be 0.001pa, 0.005pa, 0.01pa, 0.015pa, 0.02pa, 0.025pa or 0.03pa.
[0124] The inventors' in-depth research revealed that during heterogeneous bonding, if the temperature is below 1900℃, the bonding is weak and prone to defects such as voids and microcracks at the interface; if the temperature is above 2100℃, power consumption is excessive, and it has little effect on improving the bonding strength. If the gas pressure is above 0.03Pa, the vacuum level is not high, and impurities such as air can easily be introduced, affecting the bonding effect; if the gas pressure is below 0.001Pa, the requirements for system equipment are very high, resulting in high costs. Therefore, it is necessary to control the temperature and gas pressure of heterogeneous bonding within the above-mentioned ranges.
[0125] Under the above conditions, heterogeneous bonding (with all bonding surfaces being silicon surfaces) results in a small lattice mismatch between the silicon carbide transition layer and the initial silicon carbide seed crystal, leading to a very low solid-solid interface energy. This facilitates the achievement of silicon carbide bonding without an intermediate layer, promoting the formation of chemical bonds between the two and reducing the density of interface defects. It also ensures close contact between their surfaces, reducing micropores and gaps, and improving the compactness and mechanical strength of the second heterogeneous bonding structure. Furthermore, it can reduce the residual stress at the interface caused by the difference in thermal expansion between the diamond / silicon carbide composite structure and the initial silicon carbide seed crystal, preventing cracking of the second heterogeneous bonding structure.
[0126] Step S32a: After heterobonding is completed, the second heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen to form a silicon carbide seed crystal.
[0127] The annealing temperature can be 1800℃, 1820℃, 1850℃, 1880℃ or 1900℃; the annealing time can be 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h or 40h.
[0128] Further research by the inventors revealed that if the temperature exceeds the above range and annealing is below 1800℃, the effect of removing thermal stress will be poor, and the thermal stress generated by bonding cannot be effectively removed. Annealing at 1900℃ can effectively remove internal thermal stress. If the temperature continues to rise, the electricity cost will be high, which is not very meaningful. The same applies to the annealing time.
[0129] Annealing the second heterobonded structure under the above conditions can not only reduce the internal thermal stress generated during the bonding process, but also promote the physical diffusion of silicon atoms at high temperature and reduce the interfacial thermal resistance.
[0130] As another preferred embodiment of this application, forming a silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure includes step S31b.
[0131] Step S31b: Under the conditions of a temperature of 850-900℃, a gas pressure of 20-30Kpa, a flow rate of 2-20sccm for both SiH4 and CH4, and a flow rate of 200-500sccm for H2, a silicon carbide seed crystal is prepared by chemical vapor deposition on the silicon surface of the diamond / silicon carbide composite structure.
[0132] The growth time for silicon carbide seed crystals is 10–20 hours, for example, 10 hours, 12 hours, 15 hours, 18 hours, or 20 hours. The temperature can be 850℃, 860℃, 870℃, 880℃, 890℃, or 900℃; the gas pressure can be 20 kPa, 22 kPa, 25 kPa, 28 kPa, or 30 kPa; the flow rates of SiH4 and CH4 can both be 2 sccm, 4 sccm, 6 sccm, 8 sccm, 10 sccm, 12 sccm, 14 sccm, 16 sccm, 18 sccm, or 20 sccm; the flow rate of H2 can be 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, or 500 sccm.
[0133] Further research by the inventors revealed that during the chemical vapor deposition (CVD) growth of silicon carbide seed crystals, growth is very slow if the temperature is below 850℃; while growth is faster if the temperature is above 900℃, the quality of the grown silicon carbide seed crystals is poor. If the gas pressure is below 20 kPa, the plasma power density is low, resulting in a slow growth rate; while if the gas pressure is above 30 kPa, the plasma density is high, leading to a faster growth rate, but also a tendency for amorphous carbides to form.
[0134] SiH4 and CH4 are the feed gases for chemical vapor deposition (CVD) growth of silicon carbide. If the concentration is too low (flow rate less than 2 sccm), the growth rate is very slow; if the concentration is too high (flow rate greater than 20 sccm), although the growth rate is fast, the quality of the grown silicon carbide material is very poor. Hydrogen (H2) is used as a carrier gas for the feed gases and can etch amorphous silicon carbide in time. If the concentration is too low (flow rate less than 200 sccm), the growth rate is very slow; if the concentration is too high (flow rate greater than 500 sccm), hydrogen will etch away other amorphous carbide materials.
[0135] If the growth time is too short (less than 10 hours), it is impossible to produce silicon carbide seed crystals of a certain thickness; if the growth time is too long (more than 20 hours), the quality of the silicon carbide seed crystals will be low, which is not conducive to the preparation of silicon carbide composite seed crystals.
[0136] Using the above conditions, silicon carbide seed crystals can be prepared by chemical vapor deposition on the silicon surface of a diamond / silicon carbide composite structure. This not only provides a good material basis for the silicon carbide transition layer and the silicon carbide seed crystal to grow or bond homogeneously, but also prevents dislocation defects inside the diamond from extending into the silicon carbide seed crystal, thus affecting the quality of the grown silicon carbide crystal.
[0137] This application utilizes the extremely high thermal conductivity of diamond (2000-2200 W / (m·K)) to rapidly conduct the heat accumulated in the silicon carbide seed crystal along the vertical direction, thereby reducing the temperature of the silicon carbide seed crystal. During thick crystal growth, the required vertical temperature gradient is determined by the temperature difference between the diamond / silicon carbide composite structure located at the bottom of the growth chamber and the silicon carbide seed crystal located at the top of the growth chamber. The temperature of the diamond / silicon carbide composite structure is higher than that of the silicon carbide seed crystal. The greater the temperature difference, the greater the vertical temperature gradient within a certain spacing range. This vertical temperature gradient is the crystallization driving force required for the growth of thick silicon carbide crystals. The greater the vertical temperature gradient, the greater the vertical crystallization driving force, and the faster the crystal grows vertically. Thus, thick silicon carbide crystals can be grown within the same growth cycle.
[0138] The horizontal temperature gradient required during the growth of large-diameter crystals is determined by the temperature difference between the silicon carbide seed crystal located at the top of the growth chamber and the temperature of the inner wall of the growth chamber. The inner wall temperature is higher than the silicon carbide seed crystal temperature. The greater the temperature difference between the two, the greater the horizontal temperature gradient within a certain spacing range. This horizontal temperature gradient is the crystallization driving force required for the growth of large-diameter silicon carbide crystals. The greater the horizontal temperature gradient, the greater the horizontal crystallization driving force, and the faster the crystal grows in the vertical direction. In the same growth cycle, large-diameter silicon carbide crystals can be grown.
[0139] Therefore, the silicon carbide composite seed crystal provided in this application can establish a large temperature gradient in both the vertical and horizontal directions. This can accelerate the growth rate of silicon carbide crystals in the vertical direction, which is beneficial for the rapid growth of silicon carbide crystals with a thickness of more than 50 mm. It can also increase the growth rate of silicon carbide crystals in the horizontal direction, which is beneficial for the rapid expansion of the diameter of silicon carbide crystals during growth. This makes it easier to achieve the growth of large-diameter silicon carbide crystals and greatly reduces the growth cost of silicon carbide materials. In summary, the silicon carbide composite seed crystal prepared by the above method can achieve the growth of large-diameter, high-thickness, and low-cost silicon carbide crystals while ensuring the growth quality of silicon carbide crystals.
[0140] In a second aspect of this embodiment, a silicon carbide composite seed crystal is provided, which is prepared by the above-described method for preparing silicon carbide composite seed crystals.
[0141] like Figure 2 As shown, the silicon carbide composite seed crystal 10 includes a diamond substrate 11, a silicon carbide transition layer 12, and a silicon carbide seed crystal 13. The silicon carbide transition layer 12 is disposed on the diamond substrate 11, and the silicon carbide seed crystal 13 is disposed on the side of the silicon carbide transition layer 12 away from the diamond substrate 11.
[0142] In a third aspect of this embodiment, a silicon carbide crystal is provided, the silicon carbide crystal comprising the aforementioned silicon carbide composite seed crystal.
[0143] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0144] It should be noted that, unless otherwise specified in the following examples, the conditions should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0145] Example 1
[0146] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0147] S11: Provides a diamond substrate with a thickness of 300μm and a roughness of 1nm.
[0148] S12: A silicon carbide transition layer with a thickness of 10 μm was obtained by chemical vapor deposition on the surface of a diamond substrate under the conditions of temperature of 850℃, gas pressure of 20 kPa, flow rates of SiH4 and CH4 of 2 sccm and flow rate of H2 of 200 sccm for 10 h.
[0149] S13: Under the conditions of temperature of 850℃, gas pressure of 20Kpa, flow rates of SiH4 and CH4 of 2sccm and H2 flow rate of 200sccm, a silicon carbide seed crystal with a thickness of 140μm was obtained by growing on the silicon surface of the diamond / silicon carbide composite structure for 10h using chemical vapor deposition, thus obtaining the silicon carbide composite seed crystal.
[0150] Example 2
[0151] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0152] S11: Provides a diamond substrate with a thickness of 480μm and a roughness of 4nm.
[0153] S12: A silicon carbide transition layer with a thickness of 50 μm was obtained by chemical vapor deposition on the surface of a diamond substrate under the conditions of temperature of 900℃, gas pressure of 30 kPa, flow rates of SiH4 and CH4 of 20 sccm and flow rate of H2 of 500 sccm for 20 h.
[0154] S13: Under the conditions of 900℃, 30Kpa, 20sccm flow rates of SiH4 and CH4, and 500sccm flow rate of H2, a silicon carbide seed crystal with a thickness of 200μm was obtained by growing on the surface of a diamond / silicon carbide composite structure for 20h using chemical vapor deposition, thus obtaining a silicon carbide composite seed crystal.
[0155] Example 3
[0156] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0157] S11: Provides a diamond substrate with a thickness of 350μm and a roughness of 3nm.
[0158] S12: A silicon carbide transition layer with a thickness of 30 μm was obtained by chemical vapor deposition on the surface of a diamond substrate under the conditions of temperature of 875℃, gas pressure of 25 kPa, flow rates of SiH4 and CH4 of 11 sccm and flow rate of H2 of 350 sccm for 15 h.
[0159] S13: Under the conditions of temperature of 875℃, gas pressure of 25Kpa, flow rates of SiH4 and CH4 of 11sccm and H2 flow rate of 350sccm, a silicon carbide seed crystal with a thickness of 150μm was obtained by chemical vapor deposition on the surface of diamond / silicon carbide composite structure for 15h, thus obtaining silicon carbide composite seed crystal.
[0160] Example 4
[0161] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0162] S11: Provides a diamond substrate with a thickness of 300μm and a roughness of 1nm.
[0163] S12: A silicon carbide transition layer with a thickness of 10 μm was prepared by chemical vapor deposition on the surface of a diamond substrate for 10 h at a temperature of 850℃, a gas pressure of 20 kPa, a flow rate of 2 sccm for both SiH4 and CH4, and a flow rate of 200 sccm for H2.
[0164] S14: Under the conditions of 1900℃ and 0.001pa, the silicon facet of the diamond / silicon carbide composite structure is heterobonded with the silicon facet of the initial silicon carbide seed crystal to obtain a second heterobonded structure.
[0165] S15: After heterobonding is completed, the second heterobonded structure is annealed for 20 hours at an annealing temperature of 1800℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide seed crystal with a thickness of 140μm, thereby obtaining a silicon carbide composite seed crystal.
[0166] Example 5
[0167] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0168] S11: Provides a diamond substrate with a thickness of 480μm and a roughness of 4nm.
[0169] S12: A silicon carbide transition layer with a thickness of 50 μm was prepared by chemical vapor deposition on the surface of a diamond substrate for 20 h at a temperature of 900℃, a gas pressure of 30 kPa, a flow rate of 20 sccm for both SiH4 and CH4, and a flow rate of 500 sccm.
[0170] S14: Under the conditions of 2100℃ and 0.03pa, the silicon facet of the diamond / silicon carbide composite structure is heterobonded with the silicon facet of the initial silicon carbide seed crystal to obtain a second heterobonded structure.
[0171] S15: After heterobonding is completed, the second heterobonded structure is annealed for 40 hours at an annealing temperature of 1900℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide seed crystal with a thickness of 200μm, thereby obtaining a silicon carbide composite seed crystal.
[0172] Example 6
[0173] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0174] S11: Provides a diamond substrate with a thickness of 350μm and a roughness of 3nm.
[0175] S12: A silicon carbide transition layer with a thickness of 30 μm was grown on the surface of a diamond substrate by chemical vapor deposition for 15 h under the conditions of temperature of 875℃, gas pressure of 25 kPa, flow rates of SiH4 and CH4 of 11 sccm and flow rate of H2 of 350 sccm.
[0176] S14: Under the conditions of 2000℃ and 0.02pa, the silicon facet of the diamond / silicon carbide composite structure is heterobonded with the silicon facet of the initial silicon carbide seed crystal to obtain a second heterobonded structure.
[0177] S15: After heterobonding is completed, the second heterobonded structure is annealed for 30 hours at an annealing temperature of 1850℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide seed crystal with a thickness of 150μm, thereby obtaining a silicon carbide composite seed crystal.
[0178] Example 7
[0179] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0180] S11: Provides a diamond substrate with a thickness of 300μm and a roughness of 1nm.
[0181] S12: Under the conditions of 1900℃ and 0.001pa, the surface of the diamond substrate is heterobonded to the carbon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0182] S13: After heterobonding is completed, the first heterobonded structure is annealed for 20 hours at an annealing temperature of 1800℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide transition layer with a thickness of 10μm.
[0183] S14: Under the conditions of temperature of 850℃, gas pressure of 20Kpa, flow rates of SiH4 and CH4 of 2sccm and H2 flow rate of 200sccm, a silicon carbide seed crystal with a thickness of 140μm was obtained by chemical vapor deposition on the silicon surface of the diamond / silicon carbide composite structure for 10h, thus obtaining the silicon carbide composite seed crystal.
[0184] Example 8
[0185] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0186] S11: Provides a diamond substrate with a thickness of 480μm and a roughness of 4nm.
[0187] S12: Under the conditions of 2100℃ and 0.03pa, the surface of the diamond substrate is heterobonded to the carbon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0188] S13: After heterobonding is completed, the first heterobonded structure is annealed for 40 hours at an annealing temperature of 1900℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide transition layer with a thickness of 50μm.
[0189] S14: Under the conditions of 900℃, 30Kpa, 20sccm flow rates of SiH4 and CH4, and 500sccm flow rate of H2, a silicon carbide seed crystal with a thickness of 200μm was obtained by chemical vapor deposition on the surface of a diamond / silicon carbide composite structure for 20h, thus obtaining a silicon carbide composite seed crystal.
[0190] Example 9
[0191] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0192] S11: Provides a diamond substrate with a thickness of 350μm and a roughness of 3nm.
[0193] S12: Under the conditions of 2000℃ and 0.02pa, the surface of the diamond substrate is heterobonded to the carbon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0194] S13: After heterobonding is completed, the first heterobonded structure is annealed for 30 hours at an annealing temperature of 1850℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide transition layer with a thickness of 30μm.
[0195] S14: Under the conditions of temperature of 875℃, gas pressure of 25Kpa, flow rates of SiH4 and CH4 of 11sccm and H2 flow rate of 350sccm, a silicon carbide seed crystal with a thickness of 150μm was obtained by chemical vapor deposition on the surface of diamond / silicon carbide composite structure for 15h, thus obtaining silicon carbide composite seed crystal.
[0196] Example 10
[0197] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0198] S11: Provides a diamond substrate with a thickness of 300μm and a roughness of 1nm.
[0199] S12: Under the conditions of 1900℃ and 0.001pa, the surface of the diamond substrate is heterobonded to the carbon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0200] S13: After heterobonding is completed, the first heterobonded structure is annealed for 20 hours at an annealing temperature of 1800℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide transition layer with a thickness of 10μm.
[0201] S14: Under the conditions of 1900℃ and 0.001pa, the silicon facet of the diamond / silicon carbide composite structure is heterobonded with the silicon facet of the initial silicon carbide seed crystal to obtain a second heterobonded structure.
[0202] S15: After heterobonding is completed, the second heterobonded structure is annealed for 20 hours at an annealing temperature of 1800℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide seed crystal with a thickness of 140μm, so as to obtain a silicon carbide composite seed crystal.
[0203] Example 11
[0204] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0205] S11: Provides a diamond substrate with a thickness of 480μm and a roughness of 4nm.
[0206] S12: Under the conditions of 2100℃ and 0.03pa, the surface of the diamond substrate is heterobonded to the carbon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0207] S13: After heterobonding is completed, the first heterobonded structure is annealed for 40 hours at an annealing temperature of 1900℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide transition layer with a thickness of 50μm.
[0208] S14: Under the conditions of 2100℃ and 0.03pa, the silicon facet of the diamond / silicon carbide composite structure is heterobonded with the silicon facet of the initial silicon carbide seed crystal to obtain a second heterobonded structure.
[0209] S15: After heterobonding is completed, the second heterobonded structure is annealed for 40 hours at an annealing temperature of 1900℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide seed crystal with a thickness of 200μm, so as to obtain a silicon carbide composite seed crystal.
[0210] Example 12
[0211] This embodiment provides a method for preparing silicon carbide composite seed crystals, including the following steps:
[0212] S11: Provides a diamond substrate with a thickness of 350μm and a roughness of 3nm.
[0213] S12: Under the conditions of 2000℃ and 0.02pa, the surface of the diamond substrate is heterobonded to the carbon surface of the initial silicon carbide transition layer to obtain the first heterobonded structure.
[0214] S13: After heterobonding is completed, the first heterobonded structure is annealed for 30 hours at an annealing temperature of 1850℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide transition layer with a thickness of 30μm.
[0215] S14: Under the conditions of 2000℃ and 0.03pa, the silicon facet of the diamond / silicon carbide composite structure is heterobonded with the silicon facet of the initial silicon carbide seed crystal to obtain a second heterobonded structure.
[0216] S15: After heterobonding is completed, the second heterobonded structure is annealed for 30 hours at an annealing temperature of 1850℃ and an annealing atmosphere of argon or nitrogen to form a silicon carbide seed crystal with a thickness of 150μm, so as to obtain a silicon carbide composite seed crystal.
[0217] Example 13
[0218] The preparation method is similar to that in Example 11, except that a groove-shaped first microchannel is formed by etching on the silicon surface of the silicon carbide transition layer; the rest is the same and will not be described again here.
[0219] The width of the first microchannel is 5μm, the depth of the first microchannel is 30μm, and the lateral spacing of the first microchannel is 5mm.
[0220] Example 14
[0221] Similar to the preparation method in Example 11, the difference is that a raised second microchannel is formed by etching on the silicon surface of the initial silicon carbide seed crystal; the rest is the same and will not be described again here.
[0222] The width of the second microchannel is 5μm, the depth of the first microchannel is 30μm, and the lateral spacing of the first microchannel is 5mm.
[0223] Example 15
[0224] Similar to the preparation method in Example 11, the difference is that a groove-shaped first microchannel is etched on the silicon surface of the silicon carbide transition layer, and a raised second microchannel is etched on the silicon surface of the initial silicon carbide seed crystal; the rest are the same and will not be described again here.
[0225] The width of the first microchannel is 5μm, the depth of the first microchannel is 30μm, and the lateral spacing of the first microchannel is 5mm; the width of the second microchannel is 5μm, the depth of the first microchannel is 30μm, and the lateral spacing of the first microchannel is 5mm.
[0226] Silicon carbide crystals were grown using the silicon carbide composite seed crystals prepared in Examples 1-15, under the following growth conditions: growth temperature of 2200-2300℃ and pressure of 3×10⁻⁶. -3 pa-5×10-3 The growth period is 160-200 hours.
[0227] The grown silicon carbide crystals have a diameter of 200 mm and a thickness of 40 mm, with an average growth rate of 200-250 μm / hour. The grown silicon carbide crystals have a smooth surface, good light transmittance, and no polycrystalline phenomenon; these silicon carbide crystals are single 4H crystals.
[0228] Under the above growth conditions (i.e., growth temperature of 2200-2300℃, pressure of 3×10⁻⁶), -3 pa-5×10 -3 Under conditions of 160-200 hours (Pa and growth time), silicon carbide crystals were grown using pure silicon carbide seed crystals. The grown silicon carbide crystals had a diameter of 150 mm and a thickness of 30 mm, with an average growth rate of 150-200 μm / hour. The surface of the silicon carbide crystals was uneven, with poor light transmittance and polycrystalline structure.
[0229] It can be seen that, compared with existing pure silicon carbide seed crystals, the silicon carbide composite seed crystals provided in this application are used to prepare silicon carbide crystals. The average growth rate is faster, and thicker silicon carbide crystals with larger diameters can be grown. Moreover, the grown silicon carbide crystals have smooth surfaces, good light transmittance, no polycrystalline phenomenon, and better quality.
[0230] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the invention without departing from the principles and spirit of this application, and all such changes should fall within the protection scope of the claims of this application.
Claims
1. A method for preparing silicon carbide composite seed crystals, characterized in that, Includes the following steps: Provide diamond substrates; A silicon carbide transition layer is formed on the surface of the diamond substrate, and the silicon surface of the silicon carbide transition layer is moved away from the surface of the diamond substrate to obtain a diamond / silicon carbide composite structure. A silicon carbide seed crystal is formed on the silicon surface of the diamond / silicon carbide composite structure, and the carbon surface of the silicon carbide seed crystal is moved away from the silicon surface of the silicon carbide transition layer to obtain a silicon carbide composite seed crystal. The thermal conductivity of the silicon carbide transition layer is less than that of the diamond substrate, and the thermal conductivity of the silicon carbide transition layer is greater than that of the silicon carbide seed crystal; the crystal form of the silicon carbide transition layer is different from that of the silicon carbide seed crystal.
2. The preparation method according to claim 1, characterized in that, During the formation of the silicon carbide transition layer on the surface of the diamond substrate, the surface of the diamond substrate and the carbon surface of the silicon carbide transition layer are bonded together through carbon atom diffusion; the formation of the silicon carbide transition layer on the surface of the diamond substrate includes: The silicon carbide transition layer is prepared by chemical vapor deposition on the surface of the diamond substrate under the conditions of temperature 850-900℃, gas pressure 20-30kPa, flow rate of SiH4 and CH4 2-20 sccm, and flow rate of H2 200-500 sccm; wherein the growth time of the silicon carbide transition layer is 10-20h.
3. The preparation method according to claim 1, characterized in that, During the formation of the silicon carbide transition layer on the surface of the diamond substrate, the surface of the diamond substrate and the carbon surface of the silicon carbide transition layer are bonded together through carbon atom diffusion; the formation of the silicon carbide transition layer on the surface of the diamond substrate includes: Under conditions of temperature of 1900–2100℃ and pressure of 0.001–0.03Pa, the surface of the diamond substrate is heterobonded to the carbon surface of the initial silicon carbide transition layer to obtain a first heterobonded structure. After heterobonding is completed, the first heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen to form the silicon carbide transition layer.
4. The preparation method according to claim 1, characterized in that, During the process of forming a silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure, the silicon surface of the silicon carbide transition layer and the silicon surface of the silicon carbide seed crystal are bonded together through silicon atom diffusion; the formation of the silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure includes: The silicon carbide seed crystal is prepared by chemical vapor deposition on the surface of the diamond / silicon carbide composite structure under the conditions of temperature 850-900℃, gas pressure 20-30kPa, flow rate of SiH4 and CH4 2-20sccm, and flow rate of H2 200-500sccm; wherein the growth time of the silicon carbide seed crystal is 10-20h.
5. The preparation method according to claim 1, characterized in that, During the process of forming a silicon carbide seed crystal on the silicon surface of the diamond / silicon carbide composite structure, the silicon surface of the silicon carbide transition layer and the silicon surface of the silicon carbide seed crystal are bonded together through silicon atom diffusion. The formation of silicon carbide seed crystals on the silicon surface of the diamond / silicon carbide composite structure includes: Under conditions of temperature of 1900–2100℃ and pressure of 0.001–0.03Pa, the silicon facet of the diamond / silicon carbide composite structure is heterobonded to the silicon facet of the initial silicon carbide seed crystal to obtain a second heterobonded structure. After heterobonding is completed, the second heterobonded structure is annealed for 20 to 40 hours at an annealing temperature of 1800 to 1900°C and an annealing atmosphere of argon or nitrogen to form the silicon carbide seed crystal.
6. The preparation method according to any one of claims 1-5, characterized in that, After forming the silicon carbide transition layer, the method further includes: A groove-shaped first microchannel is formed on the silicon surface of the silicon carbide transition layer; or a raised first microchannel is formed on the silicon surface of the silicon carbide transition layer. Wherein, the width of the first microchannel is 5-10 μm; and / or the depth of the first microchannel is 30-50 μm; and / or the lateral spacing of the first microchannel is 5-10 mm.
7. The preparation method according to claim 6, characterized in that, Before forming the silicon carbide seed crystal, the method further includes: A groove-shaped second microchannel is formed on the silicon surface of the initial silicon carbide seed crystal; or a raised second microchannel is formed on the silicon surface of the initial silicon carbide seed crystal. Wherein, the width of the second microchannel is 5-10 μm; and / or the depth of the second microchannel is 30-50 μm; and / or the lateral spacing of the second microchannel is 5-10 mm; The raised second microchannel corresponds to the grooved first microchannel, so that the raised second microchannel can be embedded in the grooved first microchannel; The raised first microchannel corresponds to the grooved second microchannel, so that the raised first microchannel can be embedded in the grooved second microchannel.
8. The preparation method according to claim 1, characterized in that, The diamond substrate is a single-crystal diamond or a polycrystalline diamond; And / or, the thickness of the diamond substrate is 300–500 μm; And / or, the thickness of the diamond substrate is less than or equal to two-thirds of the thickness of the silicon carbide composite seed crystal, and the thickness of the diamond substrate is greater than or equal to one-half the thickness of the silicon carbide composite seed crystal. And / or, the surface roughness of the diamond substrate is less than a first preset roughness, the first preset roughness being in the range of 1 to 5 nm; And / or, the silicon carbide material in the silicon carbide transition layer is of 3C, 4H, 6H or 15R crystal form; And / or, the thickness of the silicon carbide transition layer is 10–50 μm; And / or, the surface roughness of the silicon surface of the silicon carbide transition layer is less than the second preset roughness, and the value of the second preset roughness is in the range of 1 to 5 nm; And / or, the thickness of the silicon carbide seed crystal is 100-200 μm; And / or, the thickness of the silicon carbide seed crystal is less than one-third of the thickness of the silicon carbide composite seed crystal; And / or, the surface roughness of the silicon surface of the silicon carbide seed crystal is less than a third preset roughness, the value of which is in the range of 1 to 5 nm.
Citation Information
Patent Citations
Method for optimizing growth of silicon carbide single crystals
CN106435735A